Cancer survival: left truncation and comparison of results from hospital-based cancer registry and population-based cancer registry - Chen, Jian-Guo; Chen, Hai-Zhen; Zhu, Jian; Shen, Ai-Guo; Sun, Xiang-Yang; Parkin, Donald Maxwell (Frontiers in Oncology, 2023)
Background Cancer survival is an important indicator for evaluating cancer prognosis and cancer care outcomes. The incidence dates used in calculating survival differ between population-based registries and hospital-based registries. Studies examining the effects of the left truncation of incidence dates and delayed reporting on survival estimates are scarce in real-world applications. Methods Cancer cases hospitalized at Nantong Tumor Hospital during the years 2002–2017 were traced with their records registered in the Qidong Cancer Registry. Survival was calculated using the life table method for cancer patients with the first visit dates recorded in the hospital-based cancer registry (HBR) as the diagnosis date (OSH), those with the registered dates of population-based cancer (PBR) registered as the incidence date (OSP), and those with corrected dates when the delayed report dates were calibrated (OSC). Results Among 2,636 cases, 1,307 had incidence dates registered in PBR prior to the diagnosis dates of the first hospitalization registered in HBR, while 667 cases with incidence dates registered in PBR were later than the diagnosis dates registered in HBR. The 5-year OSH, OSP, and OSC were 36.1%, 37.4%, and 39.0%, respectively. The “lost” proportion of 5-year survival due to the left truncation for HBR data was estimated to be between 3.5% and 7.4%, and the “delayed-report” proportion of 5-year survival for PBR data was found to be 4.1%. Conclusion Left truncation of survival in HBR cases was demonstrated. The pseudo-left truncation in PBR should be reduced by controlling delayed reporting and maximizing completeness. Our study provides practical references and suggestions for evaluating the survival of cancer patients with HBR and PBR.